24 Correlation of Microcirculation Analysis with Hemodynamic and Biochemical Parameters of Tisular Perfusion. (October 2012) - Gonzalez, R; Urbano, J; Solana, MJ; López, J; Botrán, M; García, A; Castillo, J Del; López-Herce, J
Abstract : Background and aims: Microcirculation assessment focus on 3 components: Vessel density, perfusion, and heterogeneity of microcirculation, measured as perfused vessel density (PVD), microcirculation flow index (MFI), proportion of perfused vessels and heterogeneity index (HI). Correlation of these parameters with hemodynamic and perfusion parameters is not well established. Methods: Prospective, observational study in 17 two-month-old sedated, relaxed and mechanically ventilated piglets (8.6±1.1kg). Video sequences were recorded using Microscan Microvision® device at three different times: before, after induced hypovolemic shock and after fluid resuscitation. 51 sets of measurements where obtained by the analysis of video sequences using automated vascular analysis software. Microcirculation was assessed determining PVD, MFI and HI. Results: PVD showed correlation with MFI (r: 0, 589) and central venous oxygen saturation (SvO2) (r:0, 383) and HI (r:-0, 600) (all p<0.01). MFI showed correlation with PVD (r:0, 589), systolic (r:0, 540), diastolic (r:0, 443), and median (r:0, 517) blood pressure, cardiac index (CI) (r:0, 578), SvO2 (r:0, 462), internal carotid artery flow (ICAF) (r:0, 623) HI (r:-0, 864), lactate blood levels (r:-0, 476) (all p<0.01), and intramural gastric pH (r:0, 352) (p:0, 028). HI showed correlation with PVD (r:-0, 600), MFI (r:-0, 864), systolic (r:-0, 359) and median (r:-0, 350) blood pressure, CI (r:-0, 389), arterial pH (r:-0, 458), SvO2 (r:-0, 492), ICAF (r:-0, 458) (all p<0.01), systemic vascular resistance index (r:0, 316) (p:0, 027) and diastolic blood pressure (r:-0, 291) (p:0, 038). Conclusions: Microcirculation parameters (PVD, MFI and IH) were consistent and related to global hemodynamic and tissue perfusion parameters.